Do informed option investors predict stock returns? Evidence from the Taiwan stock exchange - Chang, Chuang-Chang; Hsieh, Pei-Fang; Lai, Hung-Neng (Journal of Banking & Finance, 2009)
In this paper, we set out to investigate the information content of options trading using a unique dataset to examine the predictive power of the put and call positions of different types of traders in the TAIEX option market. We find that options volume, as a whole, carries no information on TAIEX spot index changes. On the other hand, however, although foreign institutional investors do not engage in much trading, there is strong evidence to show that the trading in which they do engage has significant predictive power on the underlying asset returns. We also find that foreign institutional investors have greater predictive power with regard to in near-the-money and middle-horizon options.